Tugas dan Kewenangan Petugas Pemasyarakatan Terhadap ‎Narapidana Yang Melakukan Pelanggaran Tata Tertib Di ‎Lembaga Pemasyarakatan Kelas IIb Tabanan - Ni Putu Yasintya Pradnyaswari; Deli Bunga Saravistha; I Gusti Ngurah Aristiawan (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
Penitentiary is a criminal justice system that has a strategic function as the implementation of imprisonment and at the same time as a place for fostering prisoners or people who commit crimes. Penitentiary as a place for self-guidance and self-improvement for inmates who are stumbling over cases and are related to the law. The large number of perpetrators of crimes that occurred in the correctional institutions were committed by the prisoners themselves, causing the coaching process to not run as expected. The various types of violations that occur in the Class IIB Tabanan Correctional Institution such as using a cellphone (mobile phone) in a residential block, fighting among prisoners, not following apples, carrying sharp weapons, not wearing WBP clothes (prisoners), and other violations. The purpose of this study is to determine the role of correctional officers in providing guidance to and to find out the consequences of violations committed by inmates in the Class IIB Tabanan Correctional Institution. The research method carried out by the author is empirical research, namely by looking at the facts in the field, especially related to the role of correctional officers against inmates who violate the rules of law in the Class IIB Tabanan Penitentiary